5-(Pyridin-4-yl)isophthalic acid - Yong-Fang Zhang; Qing-Fu Zhang; Juan Jin; De-Zhi Sun; Da-Qi Wang (Acta Crystallographica Section E, 2010)
In the title compound, C13H9NO4, the two carboxylic groups and the benzene ring are approximately co-planar with a maximum atomic deviation 0.175 (4) Å, while the pyridine ring is oriented at a dihedral angle of 31.07 (18)° with respect to the benzene ring. In the crystal, molecules are linked by O—H...O, O—H...N and weak C—H...O hydrogen bonds, forming a three-dimensional supramolecular framework.